2014
DOI: 10.1155/2014/583047
|View full text |Cite
|
Sign up to set email alerts
|

Development and Validation of HPTLC Method for Simultaneous Estimation of Diosgenin and Quercetin in Fenugreek Seeds (Trigonella foenum-graceum)

Abstract: A sensitive, fast, and reproducible high performance thin-layer chromatographic method has been developed for simultaneous analysis of diosgenin and quercetin from fenugreek seeds, using TLC aluminium plates precoated with silica gel G60F254. Among the different combinations of mobile phases used, best separation was achieved in Toluene-ethyl acetate-formic acid (5 : 4 : 1, v/v/v). Densitometric scanning of the plates directly at 275nm was used for analysis of quercetin. While as for analysis of diosgenin, pla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 12 publications
0
19
0
Order By: Relevance
“…Both methods were precise and specific and there was no statistical significant difference between them. Other HPTLC methods have been validated for the determination of diosgenin also in fenugreek seeds and in marketed formulations [101, 102]. In addition, by means of the HPTLC technique, the diosgenin content in fifteen different Trigonella species was determined, including seeds and aerial parts of the plant, and it can be concluded that the seeds of the species Trigonella foenum graecum present the highest diosgenin level [103].…”
Section: Methodsmentioning
confidence: 99%
“…Both methods were precise and specific and there was no statistical significant difference between them. Other HPTLC methods have been validated for the determination of diosgenin also in fenugreek seeds and in marketed formulations [101, 102]. In addition, by means of the HPTLC technique, the diosgenin content in fifteen different Trigonella species was determined, including seeds and aerial parts of the plant, and it can be concluded that the seeds of the species Trigonella foenum graecum present the highest diosgenin level [103].…”
Section: Methodsmentioning
confidence: 99%
“…[56] Diosgenin in FS were estimated through HPLC and found 29.65 μg/ml and 5.087 mg/g, respectively. [57,58]…”
Section: Solventsmentioning
confidence: 99%
“…In the accuracy study, the percent recoveries were between 98.6-99.7%, which indicated adequate reliability, repeatability, and accuracy of the method. 59 The percent RSD obtained for intraday and inter-day precision were in between 0.134-0.645, which is significant as per ICH guidelines and suggested that the method is precise. In robustness study, low present RSD was indicated that the proposed method is robust.…”
Section: Discussionmentioning
confidence: 77%